Virtual R&D teams and SMEs growth: A comparative study between Iranian and Malaysian SMEs - Ale Ebrahim, N.; Ahmed, S.; Taha, Z. (Academic Journals, 2010)
This paper explores potential advantages of using virtual teams for small and medium-sized enterprises (SMEs) with a comprehensive review on various aspects of virtual teams. Based on the standing of the pertinent literatures, attempt has been made to study the aspects by online survey method in Iran and Malaysia. In both countries, SMEs play an important role in their economies, employments, and capacity building. Virtual R&D team can be one of the means to increase SMEs efficiency and competitiveness in their local as well as global markets. In this context, surveys have been conducted to evaluate the effects of virtuality to the growth of SMEs. The study addresses some differences between two countries in engaging virtual research and development (R&D) teams in their SMEs. It is observed that there is a significant difference between the SMEs turnover that employed virtual team and that did not employ the virtual team. The way for further studies and recommend improvements are proposed.